Workplace well-being karyawan: Bagaimana peran work engagement? - Saragih, Martha Lina; Prasetyo, Yanto; Farhanindya, Hikmah Husniyah (SUKMA : Jurnal Penelitian Psikologi, 2025)
This study aims to examine the relationship between workplace well-being and work engagement among employees. Workplace well-being refers to the physical and mental well-being that employees experience in the workplace. Meanwhile, work engagement is a positive condition in which individuals demonstrate enthusiasm, dedication, and full focus in carrying out their work. This research employed a quantitative method with a correlational design. The sampling technique used was classical random sampling, with a total of 101 employees working at a regional company in Surabaya participating in the study. The research instruments utilized were the workplace well-being scale based on the theory of Hyett & Parker (2011) and the work engagement scale based on the theory of Bakker and Schaufeli (2004). The data obtained were analyzed using the Pearson Product Moment correlation test. The results showed a significant positive relationship between workplace well-being and work engagement among employees at a regional company in Surabaya. This indicates that the higher the workplace well-being, the higher the work engagement, and conversely, the lower the workplace well-being, the lower the work engagement among employees. Penelitian ini bertujuan untuk mengetahui hubungan antara workplace well-being dengan work engagement pada karyawan. Workplace well-being adalah kesejahteraan baik fisik maupun mental yang didapatkan karyawan di tempat kerja. Sementara itu, work engagement adalah kondisi positif dimana individu memiliki semangat, dedikasi dan fokus penuh dalam melaksanakan pekerjaan. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional. Teknik pengambilan sampel dilakukan dengan classical random sampling dengan jumlah partisipan sebanyak 101 laryawan yang bekerja disalah satu perusahaan daerah yang ada di Surabaya. Instrumen penelitian ini menggunakan skala workplace well-being berdasarkan teori Hyett & Parker (2011) serta skala work engagement berdasarkan teori Bakker dan Schaufeli (2004). Data yang diperoleh dianalisis menggunakan uji korelasi Pearson Product Moment. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara workplace well-bening dengan work engagement pada karyawan disalah satu perusahaan daerah yang ada di Surabaya. Hal ini mengindikasikan bahwa semakin tinggi workplace well-being maka semakin tinggi juga workengagement, demikian sebaliknya jika semakin rendah workplace well-being maka semakin rendah juga work engagement pada karyawan